Green Growth in the OECD: State of the Art - Szita Tóth, Klára (Theory, Methodology, Practice – Review of Business and Management, 2014)
The concept and initiative of green (world) economy but especially the greening of industry is not new. It appeared 20 years ago at the Rio World Summit, and since that time it has been discussed constantly, integrating more new and complex approaches, but particularly gaining focus in context with the increasing negative environmental impacts and global warming. As the advanced economic globalisation and acceleration of trade has increased the degradation of environment (damages and risk), a new strategic orientation became essential. That was the reason why a proposal at the Rio+20 World Summit initiated global environmental governance for the first time (Biermann et al. 2012). At the same time, requirements and expectations escalated to develop a green but even more a blue economy (Paoli 2010). But as the analysis of country statistics has shown, the level and status of the greening varies by countries. With the comparison of the green index and the FOI indices (Bartha - Gubik 2013a, Bartha – Gubik, 2014c)) those countries can be identified which have already made great progress in this matter and should thus be a good example to follow. It is well known that growth theories examine, analyse and explain the phenomenon and main factors of development, but they tend to consider only the economic aspects of growth, explaining and categorising the triggering factors into inside and outside factors, without giving any characteristic role to the natural environment in development. However, experts of sustainability and leading representatives of ecological economics have pointed out that the three pillars of development, based on the key issues of social well-being, should be complemented with the aspects of sustainability. This paper summarises the main steps, results and bottlenecks of the way towards green world economy.